Evaluation of accuracy of portable fingertip pulse oximeter, as compared to that of a hospital oximeter with digital sensor - Denise Pupim; Liogi Iwaki Filho; Wilton Mitsunari Takeshita; Lilian Cristina Vessoni Iwaki (Indian Journal of Dental Research, 2013)
Context: The pulse oximeter is a device that noninvasively provides continuous information about the peripheral oxygen saturation (SpO2) rate. This device is utilized in the detection of hypoxemia, due to its able to sense changes in hemoglobin oxygen saturation. Aims: The objective of this study was to verify the accuracy of the Choice® Medical MD300C3 Fingertip Pulse Oximeter, as compared to that of a hospital oximeter coupled with a Dräger® Infinity Delta monitor, with the purpose of using this first methodology in dental procedures to monitor the peripheral oxygen saturation (SpO2) of patients submitted to dental treatments. Materials and Methods: Fifty-five adult patients, both genders, were selected in the Santa Casa Hospital of Maringa, Brazil. The volunteers did not present cardiac problems, prosthetic cardiac valves, pacemakers, or pulmonary diseases, and were not pregnant or children. Each patient received a portable fingertip pulse oximeter (PPO) on the middle finger of the left hand and the hospital oximeter (control device) on the forefinger of the same hand. A total of six measurements were developed. The Pearson correlation coefficient and the Bland and Altman method was used to calculate the statistical analysis. Results: No statistically significant difference was found between the measurements taken by the utilized devices. The average of comparative analysis presented by the devices was 0.2337 ± 0.4355 (mean ± SD), suggesting a strong correlation between the obtained results. Conclusion: According to the methodology of the research, the PPO has similar accuracy to the conventional hospital oximeter with digital sensor. The PPO can be used in dental treatments.